Downshifted d‐Band Center of Ru/MWCNTs by Turbostratic Carbon Nitride for Efficient and Robust Hydrogen Evolution in Alkali. Issue 7 (21st March 2019) - Gou, Wangyan; Li, Jiayuan; Gao, Wei; Xia, Zhaoming; Zhang, Sai; Ma, Yuanyuan
Abstract: Ru, unlike Pt, is seldom considered as the effective electrocatalyst for hydrogen evolution reaction (HER) due to the strong binding of hydrogen species on metal surface as well as the serious metal bleaching. Herein, the amorphous turbostratic‐phased carbon nitride (t‐CNx ) layer was utilized to downshift the d‐band center of the Ru/multi‐walled carbon nanotubes (Ru/MWCNTs) hybrids to achieve the optimized hydrogen species adsorption for subsequent efficient and stabilized hydrogen evolution in alkali. The catalysts with a low Ru loading of 8  wt  % presented the high HER activity with a low overpotential of 39 mV for a catalytic current density of 10 mA cm −2, a small Tafel slope of 28 mV dec −1 and a stabilized catalytic performance over a period of 14 h in 1.0 M KOH, outperforming the 20  wt  % Pt/C benchmarks. The thin t‐CNx layer play dual roles: (1) as the modulator of electronic structures for Ru with lower d‐band position for the enhanced activity and (2) as the protective layer to avoid the metal aggregation/bleaching and improve the catalytic stability of the hybrid catalysts subsequently. Abstract : A shift in center ! Optimized hydrogen absorption on Ru/MWCNTs via downshifted d‐band center of Ru by encapsulating t‐CNx for HER in alkali.